STEM professional development: A decade of progress - Zuhaida, Anggun; Widodo, Ari; Prima, Eka Cahya; Solihat, Rini (Journal of Turkish Science Education, 2025)
Along with the development of STEM education at all levels of education, STEM teacher professional development (TPD) has become an important topic. This study aims to provide a comprehensive picture of the progress of STEM PD over a decade in terms of the characteristics of STEM PD publications, developments in STEM PD research, and trends in STEM PD research topics. This research presents a bibliometric analysis of STEM PD topics using VOSviewer and Microsoft Excel. Seven hundred and sixty four publications were retrieved from Scopus and used in this study. The characteristics of STEM publications show that the author who is most influential as measured by citations regarding STEM PD is Moore, T.J., the country with the most publications is the US, and the International Journal of STEM Education is the source of the journal with the highest citations. Data shows increased research development regarding STEM PD from one year to the next. The implementation of STEM PD is carried out using various methods and objectives. Trends in STEM PD research topics are associated with the keywords found. Some of these keywords show that STEM PD is closely related to the learning process, curriculum, teacher competency, and educational development. This research examines STEM PD programmes for instructors from various disciplines, their techniques, and their impacts. This study’s findings can be utilised to determine the trajectory of future research in the implementation of STEM PD and as a guide for the development of future research.